Porphyrin biosynthesis in Rhodopseudomonas palustris-XII. δ-aminolevulinate synthetase switch-off/on regulation - Viale, A.A. (1987)
The high levels of δ-aminolevulinate synthetase (ALA-S) in Rhodopseudomonas palustris cells grown anaerobically in the light (Ph) decrease to those found in cells grown aerobically in the dark (A), when the former cultures were vigorously oxygenated; simultaneously bacteriochlorophyll (Bchl) synthesis abruptly halted leading to diminished steady-state specific Bchl content. When flushing oxygen was interrupted, enzymic activity increased, whether chloramphenicol was present or not in the medium; if the protein synthesis inhibitor was added when oxygenation started, ALA-S declined in the same fashion as in its absence, but thereafter reactivation of the enzyme was lower than before. Succinyl-CoA-synthetase and ALA-dehydratase activities were also measured under the conditions described, and no changes at all have been observed. The existence of different forms of ALA-S in R. palustris depending on growth conditions is postulated along with the formation of low molecular weight factors which can modulate ALA-S activity by binding to the enzyme; a widespread mechanism in the adaptation of micro-organisms to changes in environment. It is also proposed that this particular regulatory phenomenon, could be referred to as a switch off/on mechanism controlling ALA-S activity in R. palustris. © 1987.